Analisis Kualitas dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kota Padang - Meswantri; Yusvi Diana; Yulasmi (Jurnal Informatika Ekonomi Bisnis, 2024)
Employee performance analysis is a form of activity that is used as a measuring tool to evaluate work processes. The importance of performance analysis will have an impact on the resulting work ethic to provide improvements to an organization. This research aims to analyze the influence of work quality and motivation on employee performance at the Padang City Education and Culture Office. The research dataset used was 123 employees with data collection methods, namely using the results of surveys and questionnaires. Research tools for analyzing work quality and motivation use Structural Equation Modeling (SEM) and Partial Least Square (PLS). Based on the tests that have been carried out, it was found that the Work Quality variable has a positive and significant effect on work morale. Work Motivation Variable, also has a quite significant positive impact on work morale. The Work Quality variable, has also been proven to have a positive but not significant effect on performance. Work Motivation, also plays an active role in performance. Overall, the results of the analysis have shown that work quality and motivation can have a positive influence and trend on employee performance. Based on these findings, this research can contribute to employee governance and management processes at the Padang City Education and Culture Office.